2007
DOI: 10.1177/0146167207303027
|View full text |Cite
|
Sign up to set email alerts
|

The Group as a Resource: Reducing Biased Attributions for Group Success and Failure via Group Affirmation

Abstract: Self-affirmation theory proposes that people can respond to threats to the self by affirming alternative sources of self-integrity, resulting in greater openness to self-threatening information. The present research examines this at a group level by investigating whether a group affirmation (affirming an important group value) increases acceptance of threatening group information among sports teams and fans. In Study 1, athletes exhibited a group-serving attributional bias, which was eliminated by the group af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
178
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(190 citation statements)
references
References 53 publications
7
178
1
1
Order By: Relevance
“…To test the efficacy of self-affirmation theory, Martens, Johns, Greenberg, & Schimel (2006) found that instructing female participants to write about why their most valued characteristic was personally important mitigated an induced stereotype threat. Group affirmation (affirming an important group value) demonstrates how athletes can use their team as a positive resource in response to threatening events (Sherman, Kinias, Major, Kim, & Prenovost, 2007). Other strategies that moderate the effects of stereotypes include priming female participants to write a 5-minute essay about an experience when they felt powerful (Van Loo & Rydell, 2013), internalized racial identity status attitudes (Davis, Aronson, & Salinas, 2006), thought substitution (Logel, Iserman, Davies, Quinn, & Spencer, 2009), and denying the accuracy of the stereotype or its self-relevance (von Hippel et al, 2005).…”
Section: Coping Mechanisms For Mitigating Stereotype Threatmentioning
confidence: 99%
“…To test the efficacy of self-affirmation theory, Martens, Johns, Greenberg, & Schimel (2006) found that instructing female participants to write about why their most valued characteristic was personally important mitigated an induced stereotype threat. Group affirmation (affirming an important group value) demonstrates how athletes can use their team as a positive resource in response to threatening events (Sherman, Kinias, Major, Kim, & Prenovost, 2007). Other strategies that moderate the effects of stereotypes include priming female participants to write a 5-minute essay about an experience when they felt powerful (Van Loo & Rydell, 2013), internalized racial identity status attitudes (Davis, Aronson, & Salinas, 2006), thought substitution (Logel, Iserman, Davies, Quinn, & Spencer, 2009), and denying the accuracy of the stereotype or its self-relevance (von Hippel et al, 2005).…”
Section: Coping Mechanisms For Mitigating Stereotype Threatmentioning
confidence: 99%
“…There is good support for a relationship between team attributions and self-esteem in team sport (Green & Holman, 2004;Sherman & Kim, 2005;Sherman, Kinias, Major, Kim, & Prenovost, 2007) and several experimental studies have demonstrated that a greater use of team-serving attributions causes subsequent increases in social self-esteem (Smurda et al, 2006). A related emotion, pride, has also been assessed in attribution research (Tracy & Robins, 2007;Nickel & Spink, 2010).…”
Section: Affective Consequencesmentioning
confidence: 99%
“…Affirming an important group value in teams has been shown to increase acceptance of threatening team information and reduce group-serving biases (Sherman et al, 2007). On the other hand, our research reveals that affirming an individual's self-views through one's own personal relationships prior to completing a team task can carry over to the group-level phenomenon.…”
Section: Theoretical Contributionsmentioning
confidence: 63%